Quenched QCD with O(a) improvement: The spectrum of light hadrons - RYAN, SINEAD MARIE (American Physical Society, 2000)
We present a comprehensive study of the masses of pseudoscalar and vector mesons, as well as octet and decuplet baryons computed in O(a)-improved quenched lattice QCD. Results have been obtained using the nonperturbative definition of the improvement coefficient csw , and also its estimate in tadpole improved perturbation theory. We investigate effects of improvement on the incidence of exceptional configurations, mass splittings, and the parameter J. By combining the results obtained using nonperturbative and tadpole improvement in a simultaneous continuum extrapolation, we can compare our spectral data to experiment. We confirm earlier findings by the CP-PACS Collaboration that the quenched light hadron spectrum agrees with experiment at the 10% level.
PUBLISHED
Keywords: Pure & Applied Mathematics